FEMINISM SPIRIT™S REFLECTIONS ON ˜JORDAN O™NEIL™ IN G.I JANE MOVIE (LINGUISTICA, 2015)
This study deals with feminism Spirit™s reflections on ˜Jordan O™Neil™ in G.I Janemovie. The study is conducted by using descriptive qualitative approach. Theobjectives of the study are to find out kinds of oppression faced by O™Neil and herfeminism spirit™s reflections in term of oppression that she had faced. The data arecollected from dialogues and scenes in the movie. The object of the study isJordan O™Neil as the female main character. The study revealed that there arethree major oppressions faced by O™Neil according to Young™s theory: beingmarginalized,exploited and experiencing powerlessness. Feminism Spirit™sreflections on Jordan O™Neil in term of oppression that she had already faced arethree major parts: being persistent, independent, and courageous.